2021
DOI: 10.21301/eap.v16i3.3
|View full text |Cite
|
Sign up to set email alerts
|

Alien and Storytelling in the Anthropocene: Evolutionism, Creationism and Pseudoarchaeology in Science Fiction

Abstract: This paper analyses the change in the metanarrative of the Alien franchise initiated by the movie Alien (1979), directed by Ridley Scott, and continued with a series of three sequels. The franchise was revived in 2012 with the prequel Prometheus. The story of the first four movies is set at the end of the anthropocene, and it deals with the horror of alien life forms, offering an evolutionist approach to the development of the human species. However, the revival of the franchise with the movie Prometheus chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The archaeologists present their findings at a meeting, and, in a typical pseudoarchaeological manner, they connect the representation from the cave on the Isle of Skye in Scotland with later representations from different cultures all over the world. They supposedly found the same representation of six circles on an Egyptian papyrus from 2470 BCE, a Mayan stela from 620 CE and on a Sumerian monument from the beginning of the third millennium BCE (Matić and Žakula, 2021). There is both a supernatural and hyperdiffusionist representation within the film, portraying inaccurate representations of archaeology and of history.…”
Section: Popular Media Representations Of Archaeology Film and Televi...mentioning
confidence: 96%
See 1 more Smart Citation
“…The archaeologists present their findings at a meeting, and, in a typical pseudoarchaeological manner, they connect the representation from the cave on the Isle of Skye in Scotland with later representations from different cultures all over the world. They supposedly found the same representation of six circles on an Egyptian papyrus from 2470 BCE, a Mayan stela from 620 CE and on a Sumerian monument from the beginning of the third millennium BCE (Matić and Žakula, 2021). There is both a supernatural and hyperdiffusionist representation within the film, portraying inaccurate representations of archaeology and of history.…”
Section: Popular Media Representations Of Archaeology Film and Televi...mentioning
confidence: 96%
“…Narratives that remove this autonomy completely disregard the research of scientists and scholars attempting to understand human cultures in the past and present, human evolution, and the development of society to today. Perhaps unintentional, these theories are proposed in favor of a problematic and colonialist origin story, deeply rooted in racist narratives of "great civilizers," bringing knowledge and technology to the "unenlightened savages" (Matić and Žakula, 2021). None of the structures on Ancient Aliens were built by non-white or Indigenous peoples in favour of a racist and colonialist narrative (Card and Anderson, 2016;.…”
Section: Consequential Ignorance: the Rise Of White Supremacy And Sci...mentioning
confidence: 99%
“…When we find the same idea outside of this realm, we tend to label it as belief, and hence unreal. However, more often than not, anthropological and archaeological analyses of various works of fiction have demonstrated that although imagined, the worlds, characters, and stories we find in fiction somehow seem awfully similar to us (Matić 2015;Matić and Žakula 2021;Žakula and Matić 2023). This is because creators of fiction frequently address ongoing problems in the real world by transferring them into an imaginary world.…”
Section: Introductionmentioning
confidence: 98%